Partial restoration of chiral symmetry in cold nuclear matter: the phi-meson case - Cobos-Martinez, J. J.; Tsushima, K.; Krein, G. [UNESP]; Thomas, A. W.; IOP (Iop Publishing Ltd, 2017)
The work presented at this workshop is divided into two parts. In the first part, the mass and decay width of the phi-meson in cold nuclear matter are computed in an effective Lagrangian approach. The medium dependence of these properties are obtained by evaluating kaon-antikaon loop contributions to the phi-meson self-energy, employing medium-modified kaon masses calculated using the quark-meson coupling model. The loop integral is regularized with a dipole form factor, and the sensitivity of the results to the choice of cutoff mass in the form factor is investigated. At normal nuclear matter density, we find a downward shift of the phi mass by a few percent, while the decay width is enhanced by an order of magnitude. Our results support the literature which suggest that one should observe a small downward mass shift and a large broadening of the decay width. In the second part, we present phi-meson-nucleus bound state energies and absorption widths for four selected nuclei, calculated by solving the Klein-Gordon equation with complex optical potentials. The attractive potential for the phi-meson in the nuclear medium originates from the in-medium enhanced K (K) over bar loop in the phi-meson self-energy. The results suggest that the phi-meson should form bound states with all the nuclei considered. However, the identification of the signal for these predicted bound states will need careful investigation because of their sizable absorption widths.